2016
DOI: 10.15268/ksim.2016.4.1.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Stretching Exercise of Hamstring Muscle on Flexibility and Foot Pressure in Subjects with and without Pelvis Neutral Position

Abstract: Purpose : The purpose of this study was to investigate the effects of flexibility and foot pressure on stretching exercise of hamstring muscle with and without pelvis neutral position. Methods :This study was performed on 30 subjects. Thirty subjects were divided into two group; hamstring passive stretching exercise with pelvis neutral position(n=15), hamstring passive stretching exercise without pelvis neutral position(n=15). Both of the group performed the exercise 4 times a week for 6 weeks. The data was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a study by Kim and Kim [30], it was confirmed that the immediate effect of stretching the hamstring muscles caused decreased muscle stiffness and a significant increase in the range of motion of the knee joint. According to a study by Jo et al [31], the manual extension of the hamstring muscle was effective in increasing the flexibility of the hamstrings while maintaining pelvic neutrality.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kim and Kim [30], it was confirmed that the immediate effect of stretching the hamstring muscles caused decreased muscle stiffness and a significant increase in the range of motion of the knee joint. According to a study by Jo et al [31], the manual extension of the hamstring muscle was effective in increasing the flexibility of the hamstrings while maintaining pelvic neutrality.…”
Section: Discussionmentioning
confidence: 99%